ANALISIS PENGARUH TARIF PARKIR DAN VOLUME PARKIR TERHADAP TINGKAT PENDAPATAN JURU PARKIR DI KOTA MATARAM - Fathurrahman Fathurrahman (Valid: Jurnal Ilmiah, 2016)
This study entitled "Analysis of Factors Affecting Income Level Interpreter Mataram City Centre". The purpose of this study was to determine the effect of parking rates and volumes partially parked on the income of parking attendants in Mataram. And to determine the effect of parking rates and parking volume predominantly to earnings parking attendants in Mataram. The method used in this study is a sample survey method is a study of a portion of the parking attendants population in Sub Cakranegara Mataram. In this study the number of parking attendants who researched many as 25 respondents. The analysis technique used multiple linear regression analysis. Regression analysis partially on variable parking rates indicate that the test is smaller than t-table, this means parking rates partially no effect on incomeMataram. Meanwhile City parking attendants parking volume variable indicates that the t-count is greater than t tables, this means the partial volume effect on the parking revenues parking attendants Mataram. From both of these variables indicate that the value of the variable parking volume greater than the value of the variable parking rates, this means that the variable volume parking most dominant influence on the income of parking attendants in Mataram. While the simultaneous regression analysis results indicate that the F-count is greater than the F-table means variable parking rates and variable volume parking simultaneous and significant effect on the income of parking attendants in Mataram